The Stream of Consciousness in the Modernist Narrative: Linguistic Architectonics and Authorial Implications (Proceedings of Southern Federal University. Philology, 2019)
Ilya S. Korostov, Igor A. Kudryashov (Rostov-on-Don, Russian Federation)The article investigates the narrative technique of the stream of consciousness and the linguistic means of its expression on the material of modernist novels by J. Joyce’s «Ulysses», and V. Woolf «Mrs. Dalloway». It is established that J. Joyce focuses on the Freudian realm of the unconscious, W. Wolf analyzes the shift of thoughts in the temporal plane – from the present to the past. Both the artistic text are based on the spontaneous flow of ideas, images and emotions, verbalizing a kind of psychonarration. By modeling internal monologues, the modernist authors provide the reader with access to the mental deep structures of the mediating characters’ consciousness, to their innermost dreams, fears and needs, presented in the text as the preverbal phase of the speech embodiment. Revealing a unique artistic originality, the texts of the novels analyzed in the article, have a general fundamental methodological feature: the characters’ mental activity is represented mainly as a slow flow of thoughts, the flow of consciousness. In the context of the modernist novel, the unconscious sphere of the character finds its exhaustive expression, in which the author’s interpretation of two fundamental methods of psychoanalysis – the study of dreams and associative thinking is traced.On the material of modernist texts, we not only traced some contrast in the semantic content of the stream of consciousness and the means of its linguistic expression, but also identified the common thematic denominator underlying this narrative technique, namely the subjective perspective of fixing everyday experience and assessing the surrounding reality. J. Joyce and V. Woolf’s characters spontaneously reproduce the everyday world through the individual perception of facts, objects and phenomena, cognitive filter of their consciousness. As a result, for them it does not matter what the world really looks like, the sphere of their habitat is phenomenological reality, which is a product of the psyche (cf. with A. Schopenhauer’s judgment «the world is my representation»). The stream of consciousness appears as a verbal channel of understanding of a person living in the modernist era.Key words: modernist text, stream of consciousness, expressive language function, narrator’s image identification, subjectivity. DOI 10.23683/1995-0640-2019-4-62-71